Cytogenetic Effects of Chronic Methylphenidate Treatment and Chronic Social Stress in Adults with Attention-Deficit/Hyperactivity Disorder - Kittel-Schneider, S.; Spiegel, S.; Renner, T.; Romanos, M.; Reif, A.; Reichert, S.; Heupel, J.; Schnetzler, L.; Stopper, H.; Jacob, C. (Pharmacopsychiatry, 2016)
Introduction: Methylphenidate (MPH) is widely used to treat childhood and adult attention-deficit/hyperactivity disorder (ADHD). However, there are still safety concerns about side effects in long-term treatment. The aim of this study was to assess cytogenetic effects of chronic MPH treatment in adult ADHD and to find out if chronic social stress is attenuated by medication and to investigate whether chronic psychosocial stress leads to mutagenic effects by itself.Methods: Lymphocytes for micronucleus assay and saliva samples for cortisol measurement were collected from adult ADHD patients and healthy controls. Stress exposure of the last 3 months was assessed by TICS (Trier Inventory for Chronic Stress).Results: We could not detect an influence of MPH treatment on cytogenetic markers. ADHD patients displayed significantly higher chronic stress levels measured by TICS compared to healthy controls which were influenced by duration of MPH treatment. ADHD patients also showed significantly lower basal cortisol levels.Discussion: We could corroborate that there are neither cytogenetic effects of chronic stress nor of chronic MPH intake even after several years of treatment.
Keywords: stress; adult attention-deficit/hyperactivity disorder; cortisol